Internal and External Predictors of Vocational High School Students’ Employability: The Role and Functions of School Counselors - Inavatin, Dira; Muarifah, Alif; Hidayah, Nurul (Psikopedagogia, 2020)
The purpose of this study was to depict the vocational high school students’ employability. Family support and self-confidence were examined as predictors that can enhance students’ readiness to enter the working world. Ninety-two students of Class XII of a vocational high school participated in this correlational study. They were recruited using cluster random sampling technique. In collecting the data, employability, self-confidence, and family support scales were administered. The collected data were analyzed using multiple regression technique. The result of the study showed that self-confidence and family support are positively correlated with employability, either partially or simultaneously. This study found that self-confidence, as the internal factor, give greater contribution to students’ employability.  The result of this study could be used as a reference for school counselors to provide guidance and counseling services to enhance students’ employability.